PENGARUH COMPELLED BODYWEIGHT SHIFT DAN SWISS BALL TERHADAP KESEIMBANGAN PADA PASIEN PASCA STROKE - heriyanto, hendri; Ega Mawarni; sahran (JURNAL PENELITIAN TERAPAN KESEHATAN, 2025)
Non-communicable diseases have undergone a shift in pattern, evidenced by an increase in mortality and morbidity rates, one of which is stroke. Approximately 85% of stroke patients experience balance disorders, with the lower extremities affected in about 50% of cases. Two non-pharmacological interventions, Compelled Bodyweight Shift and Swiss Ball, are known to improve balance in stroke patients. This study aims to determine the effect of Compelled Bodyweight Shift and Swiss Ball therapy on improving balance in stroke patients. The study used a quasi-experimental pretest and posttest design with a control group. The sampling technique used was purposive sampling with a total sample of 40 participants. The intervention group received Compelled Bodyweight Shift and Swiss Ball therapy, while the control group received heel raise exercises. The average balance score of the intervention group was 25.65, increasing to 31.50, and the control group was 28.00, increasing to 32.91. Statistical analysis using the Mann-Whitney U test yielded a p-value of 0.005 (p-value <0.05), indicating that Compelled Bodyweight Shift and Swiss Ball therapy are effective in improving balance. Compelled Bodyweight Shift and Swiss Ball therapy significantly improved balance in stroke patients and can be recommended as non-pharmacological physical exercise